Inflammatory-driven NK cell maturation and its impact on pathology - Bourayou, Elsa; Golub, Rachel (Frontiers in Immunology, 2022)
NK cells are innate lymphocytes involved in a large variety of contexts and are crucial in the immunity to intracellular pathogens as well as cancer due to their ability to kill infected or malignant cells. Thus, they harbor a strong potential for clinical and therapeutic use. NK cells do not require antigen exposure to get activated; their functional response is rather based on a balance between inhibitory/activating signals and on the diversity of germline-encoded receptors they express. In order to reach optimal functional status, NK cells go through a step-wise development in the bone marrow before their egress, and dissemination into peripheral organs via the circulation. In this review, we summarize bone marrow NK cell developmental stages and list key factors involved in their differentiation before presenting newly discovered and emerging factors that regulate NK cell central and peripheral maturation. Lastly, we focus on the impact inflammatory contexts themselves can have on NK cell development and functional maturation.